CircRNA‐0077930 from hyperglycaemia‐stimulated vascular endothelial cell exosomes regulates senescence in vascular smooth muscle cells - Wang, Sha; Zhan, Junkun; Lin, Xiao; Wang, Yanjiao; Wang, Yi; Liu, Youshuo (Cell biochemistry and function, 2020)
Vascular smooth muscle aging leads to diabetic complications such as cardiovascular and kidney diseases or diabetic foot. Therefore, understanding the mechanism of smooth muscle cell senescence in a high‐glucose (HG) environment is essential. The purpose of this study was to determine whether and how circRNA from human umbilical vein endothelial cell exosomes (HUVEC‐Exos) under HG conditions regulates the senescence of vascular smooth muscle cells (VSMCs). Combining circRNA array analysis and bioinformatics, we postulated that the circRNA‐0077930‐miR‐622‐Kras CeRNA network plays an important role in inducing senescence in VSMCs. CircRNA‐0077930 transmitted by HG‐HUVEs‐Exos induced senescence of VSMCs by down‐regulation of miR‐622 expression and up‐regulation of Kras, p21, p53 and p16 expression. Moreover, the lactate dehydrogenase (LDH) activity was significantly increased while anti‐oxidative stress marker (superoxide dismutase, SOD) activity was reduced in HG‐HUVEC‐Exos treatment VSMCs. Finally, HG‐HUVEC‐Exos with depleted‐circRNA‐0077930 is no longer able to induce cellular senescence in VSMCs. These findings provided a new light on the effective treatment of VSMC senescence. Significance of the study Previous studies have shown that endothelial cell senescence is closely related to smooth muscle cell aging. Here, for the first time, we proved that the HG‐HUVECs derived exosomes induced the VSMCs senescence by circRNA0077930‐miR622‐Kras CeRNA network. The circRNA‐0077930‐depleted exosomes would lose the ability to promote cellular senescence of VSMCs.